Profiling of Metabolites of Bacillus spp. and Their Application in Sustainable Plant Growth Promotion and Biocontrol - Shahid, Izzah; Han, Jun; Hanooq, Sharoon; Malik, Kauser A.; Borchers, Christoph H.; Mehnaz, Samina (Frontiers in Sustainable Food Systems, 2021)
Bacillus spp. are well-characterized as efficient bioinoculants for sustainable plant growth promotion and biocontrol of phytopathogens. Members of this spp. exhibit the multifaceted beneficial traits that are involved in plant nutrition and antimicrobial activities against phytopathogens. Keeping in view their diverse potential, this study targeted the detailed characterization of three root-colonizing Bacillus strains namely B. amyloliquefaciens, B. subtilis, and B. tequilensis, characterized based on 16S rRNA sequencing homology. The strains exhibited better plant growth promotion and potent broad-spectrum antifungal activities and exerted 43–86% in-vitro inhibition of growth of eight fungal pathogens. All strains produced indole acetic acid (IAA) in the range of 0.067–0.147 μM and were positive for the production of extracellular enzymes such as cellulase, lipase, and protease. Ultra-performance Liquid Chromatography-Electrospray Ionization-Mass Spectrometry (UPLC-ESI-MS/MS) analysis revealed the production of antifungal metabolites (AFMs) such as surfactins, iturins, fengycins, macrolactins, bacillomycin-D, and catechol-based siderophore bacillibactin which were further confirmed by amplifying the genes involved in the biosynthesis of these antimicrobial lipopeptides. When compared for the amounts of different cyclic-peptides produced by three Bacillus strains, B. amyloliquefaciens SB-1 showed the most noticeable amounts of all the antifungal compounds. Plant experiment results revealed that inoculation with phytohormone producing Bacillus spp. strains demonstrated substantial growth improvement of wheat biomass, number of spikes, and dry weight of shoots and roots. Results of this study indicate the biocontrol and biofertilizer potential of Bacillus spp. for sustainable plant nutrient management, growth promotion, and effective biocontrol of crop plants, particularly cultivated in the South Asian region.